2020
DOI: 10.1088/1755-1315/578/1/012013
|View full text |Cite
|
Sign up to set email alerts
|

The LED phyto lighting for improving the environmental friendliness of growing and productivity of lettuce varieties with red and green leaves

Abstract: The intensively developing area of modern phytophysiology is the ecological plants physiology, which important section is the ecology of photosynthesis, by which we understand the intensity and photosynthesis productivity dependence on environmental factors, primarily on optical radiation. The urgent problem of growing plants under artificial conditions is to increase energy efficiency, reduce energy intensity and degree of environmental impact. Using LED irradiators with the function of controlling the spectr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 17 publications
0
3
0
1
Order By: Relevance
“…However, Lin et al (2013) and Proshkin et al (2020) did not find significant differences in pigment contents (CHL a, b, and CAR) regardless of the light spectrum. On the other hand, Proshkin et al (2020) indicated that under low light conditions in a greenhouse and a minor blue light fraction, red lettuce leaves tend to remain green as ANT accumulation is lower. Other studies showed that a combination of red and blue or red, blue, and green LED lights induced ANTs contents (Stutte et al, 2009).…”
Section: Introductionmentioning
confidence: 59%
See 2 more Smart Citations
“…However, Lin et al (2013) and Proshkin et al (2020) did not find significant differences in pigment contents (CHL a, b, and CAR) regardless of the light spectrum. On the other hand, Proshkin et al (2020) indicated that under low light conditions in a greenhouse and a minor blue light fraction, red lettuce leaves tend to remain green as ANT accumulation is lower. Other studies showed that a combination of red and blue or red, blue, and green LED lights induced ANTs contents (Stutte et al, 2009).…”
Section: Introductionmentioning
confidence: 59%
“…A combination of red and blue LEDs improved CHL content in lettuce (Lee et al, 2016;Choong et al, 2018) and red light alone (Son and Oh, 2013). However, Lin et al (2013) and Proshkin et al (2020) did not find significant differences in pigment contents (CHL a, b, and CAR) regardless of the light spectrum. On the other hand, Proshkin et al (2020) indicated that under low light conditions in a greenhouse and a minor blue light fraction, red lettuce leaves tend to remain green as ANT accumulation is lower.…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…Диапазон длин волн излучения светодиодов в красной области спектра составляет 620-680 нм, в оранжевой -610-620 нм, в желтой -585-595 нм, в зеленой -520-535 нм, в голубой -465-475 нм, в синей -450-465 нм и в ультрафиолетовой 370-400 нм (Айзенберг Ю.Ф., 2006). Изменяя ток для разных светодиодов, можно получать различные по составу и интенсивности спектры излучения и таким образом подбирать спектр светильника в зависимости от конкретного этапа развития растения [14][15][16].…”
unclassified